Responsible Leadership Effect on Career Success: The Role of Work Engagement and Self-Enhancement Motives in the Education Sector - Li, Minyan; Yang, Feng; Akhtar, Muhammad Waheed (Frontiers in Psychology, 2022)
Using social information processing theory, our study investigates the effect of responsible leadership on employee career success via work engagement. The model also examines whether self-enhancement motives moderate the aforementioned mediating linkages. In three waves, data were collected from employees in the education sector. Macro PROCESS was used to assess the hypotheses. According to the findings, responsible leadership boosts employee work engagement, which leads to career success. The results also suggest that responsible leadership has a stronger positive effect on work engagement among individuals high on self-enhancement motives. There is no evidence in the educational literature about the underlying process through which a responsible leadership impacts employee success. Our research addresses this gap by suggesting work engagement as a mediator of the effect of responsible leadership on individuals’ career success at various degrees of self-enhancement motives.